Intestinal fatty acid binding protein is associated with coronary artery disease in long-term type 1 diabetes—the Dialong study - Marte Narum; Ingebjørg Seljeflot; Vibeke Bratseth; Tore Julsrud Berg; Kari Anne Sveen (Cardiovascular Diabetology)
Abstract Background Individuals with type 1 diabetes are at increased risk of accelerated atherosclerosis, causing coronary artery disease (CAD). The underlying mechanisms remain unclear, but new theories proposed are damage of gut mucosa causing leakage and translocation of gut microbiota products into the circulation, leading to inflammatory responses and atherosclerosis. We therefore aimed to study the associations between gut related inflammatory biomarkers and coronary atherosclerosis in individuals with long-term type 1 diabetes. Methods In this cross-sectional, controlled study of 102 participants with type 1 diabetes and 63 control subjects, we measured circulating levels of intestinal fatty acid binding protein (I-FABP), soluble cluster of differentiation 14 (sCD14), lipopolysaccharide binding protein (LBP) and interleukin 18 (IL-18) by enzyme-linked immunosorbent assay (ELISA), and further gene expression of CD14 and toll-like receptor 4 (TLR4) by real time PCR in circulating leukocytes and peripheral blood mononuclear cells (PBMCs). The participants had either established coronary heart disease (CHD) or underwent computed tomography coronary angiography (CTCA) to assess for coronary atherosclerosis, including total, calcified and soft/mixed plaque volumes. Results In the diabetes group, the levels of I-FABP were significantly higher in participants with established CHD or significant stenosis on CTCA compared to the participants with normal arteries or non-significant stenosis, with median 1.67 ng/ml (interquartile range [IQR] 1.02–2.32) vs. median 1.09 ng/ml (IQR 0.82–1.58), p = 0.003. I-FABP was associated with significant coronary artery stenosis by CTCA (> 50%) or previously established CHD in the adjusted analysis (odds ratio [OR] = 2.32, 95% confidence interval [CI]: 1.09–4.95; p = 0.029). The levels of I-FABP correlated also to total coronary plaque volume (r = 0.22, p < 0.05). This association remained significant after adjusting for age, sex, persistent albuminuria, eGFR, statin treatment, diabetes duration and mean time-weighted variables; HbA1c, LDL-cholesterol and systolic blood pressure (OR = 1.97, 95% CI: 1.28–3.01; p = 0.002). Conclusions In this cohort of individuals with long-term type 1 diabetes I-FABP associated significantly with coronary artery stenosis, suggesting a potential role of gut mucosa damage in the process of atherosclerosis in type 1 diabetes.